2019
DOI: 10.1126/science.aax6998
|View full text |Cite
|
Sign up to set email alerts
|

An oxyl/oxo mechanism for oxygen-oxygen coupling in PSII revealed by an x-ray free-electron laser

Abstract: Photosynthetic water oxidation is catalyzed by the Mn4CaO5 cluster of photosystem II (PSII) with linear progression through five S-state intermediates (S0 to S4). To reveal the mechanism of water oxidation, we analyzed structures of PSII in the S1, S2, and S3 states by x-ray free-electron laser serial crystallography. No insertion of water was found in S2, but flipping of D1 Glu189 upon transition to S3 leads to the opening of a water channel and provides a space for incorporation of an additional oxygen ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

38
462
8

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 295 publications
(508 citation statements)
references
References 45 publications
38
462
8
Order By: Relevance
“…This gives rise to equivalent values of the temperature factors between the two equivalent atoms in the multiple model, and this population of S 2 and S 1 -states after one-ash illumination is similar to the e ciencies of the S i -state transition estimated by the Fourier transform infrared spectroscophy 7,20 . The OEC structures in the S 1 and S 2 states determined in the present study are similar to those reported in the previous studies 8,9 . The OEC structure in the S 2 state was in the open-cubane form, in which the right side of the O5 is open, giving rise to the ve-coordinate trigonal bipyramidal coordination of Mn1.…”
Section: Structural Determination Of Psii In the S 2 Statesupporting
confidence: 91%
See 3 more Smart Citations
“…This gives rise to equivalent values of the temperature factors between the two equivalent atoms in the multiple model, and this population of S 2 and S 1 -states after one-ash illumination is similar to the e ciencies of the S i -state transition estimated by the Fourier transform infrared spectroscophy 7,20 . The OEC structures in the S 1 and S 2 states determined in the present study are similar to those reported in the previous studies 8,9 . The OEC structure in the S 2 state was in the open-cubane form, in which the right side of the O5 is open, giving rise to the ve-coordinate trigonal bipyramidal coordination of Mn1.…”
Section: Structural Determination Of Psii In the S 2 Statesupporting
confidence: 91%
“…4). However, the changes found in the isomorphous difference Fourier map, such as the shorting of Mn3-Mn4 and elongations of Mn1-Mn3, Mn3-Ca, and Mn4-Ca, were consistent with the previous study with the diffraction data collected at 100 K for the room temperature-trapped S 2 -state 8 (Fig. 4 and Table 2).…”
Section: Structural Determination Of Psii In the S 2 Statesupporting
confidence: 91%
See 2 more Smart Citations
“…In natural photosystem II (PSII), a tetra-manganese-calcium molecular cluster (Mn 4 CaO 5 ) serves as the active center to split water for oxygen evolution with generation of four protons and electrons (2H 2 O / O 2 + 4H + + 4e À ) (Ferreira et al, 2004;Umena et al, 2011;Yano and Yachandra, 2014;Suga et al, 2019). The astonishing activity and stability of the oxygen evolution complex (OEC-PSII) stimulate the scientific community to develop artificial molecular catalysts that are sufficiently rugged and efficient to remove four electrons and four protons for water oxidation (Concepcion et al, 2009;Inoue et al, 2011;Garrido-Barros et al, 2017).…”
Section: Introductionmentioning
confidence: 99%